Pengaruh Kepuasan Kerja Terhadap Komitmen Organisasional dan Kinerja Karyawan Koperasi Krama Bali - dana, pramitha; wayan gede, supartha; gede, riana (E-Jurnal Manajemen, 2012)
ABSTRACT The problem often faced by companies related to the human resource potential resource is maintained to keep a commitment and improved performance. Phenomenon that often occurs in the performance of a company that has been so good can be destroyed, either directly or indirectly affected by the level of employee satisfaction. This study aims to analyze the effect of job satisfaction to organizational commitment and employee performance. There are 129 respondents for the samples employees of Koperasi Krama Bali. From the results of this study proved that the positive effect on job satisfaction organizational commitment, which means that the higher the level of job satisfaction organizational commitment is increasing. Organizational commitment proved positive but not significant effect on the performance, the higher the organizational commitment of employees the motivation to improve performance, but this does not happen in practice. Job satisfaction proved to have a positive impact on employee performance, which means that the higher the job satisfaction of employees, the more motivated the employees to improve their performance as well. To increase the organizational and employee performance, the implications that can be carried out by Koperasi Krama Bali is to increase employee job satisfaction.   Keywords: Job satisfaction, organizational commitment, employee performance